If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -18 = -12 Reorder the terms: -18 + -6x = -12 Solving -18 + -6x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -6x = -12 + 18 Combine like terms: -18 + 18 = 0 0 + -6x = -12 + 18 -6x = -12 + 18 Combine like terms: -12 + 18 = 6 -6x = 6 Divide each side by '-6'. x = -1 Simplifying x = -1
| -(6n-4)=-7(2n+3)+3n | | 13x+7x=106 | | 3(X*5)=120 | | 13x+7s=106 | | x^2+20=8 | | 2x+2=92 | | 12/x=2/50 | | -4+f=18 | | 3x-24+15=-18 | | 50+105x=14.75x | | 3x-24+15=18 | | 3.95+3b=33.80 | | -34=v+43-5v | | 2(2x+4)=-4(x-16) | | 57.2+a*x+b*yandx+y=1 | | 2.5x+20=3x-4 | | X-11=-6 | | -2x+18=3x+33 | | 45b=25 | | (7y-8)-(5+6y)=9 | | 7=35n | | 95+13x+5=3x+10 | | -5.2=3w-3.4w | | 300x^2-240x+32=0 | | 5-8.5x=6.7-7.5x | | 4m-15=33 | | 3z+3=4z-14 | | y=2x^2-5x-42 | | 2w(w+2w)=18 | | y=2x^2-5x-43 | | -5x(x+y)=20+3x | | 5-7=d |